1991
DOI: 10.1111/j.1439-0418.1991.tb01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Spanish strain of Agrotis segetum granulosis virus (Baculoviridae) against Agrotis segetum Schiff. (Lep., Noctuidae) on corn

Abstract: The efficacy of a granulosis virus isolated in Spain from Agrotis segetum larvae (AsGV) was field tested and compared with chlorpyrifos and flucythrinate as control agents against A. segetum larvae on corn seedlings. The application of the AsGV through bran wheat bait provided a crop protection similar to that produced by chlorpyrifos and flucythrinate. Significant differences were not found between the levels of protection provided by AsGV when it was applied at a rate of 4.1 × 1012 IB/ha or 4.1 × 1013 IB/ha.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…AsNPV was app1ied at arate of 4 x 1012 po1yhedra/ha and AsGV at 4 x 1013 granu1es/ha. The doses were fue same for both spray and bait treatments and were chosen from experience with previous trials (Caballero et al, 1990(Caballero et al, , 1991Bourner, unpub1ished data). The virus treatments were carried out on 27 May 1991.…”
Section: Insectsmentioning
confidence: 99%
See 2 more Smart Citations
“…AsNPV was app1ied at arate of 4 x 1012 po1yhedra/ha and AsGV at 4 x 1013 granu1es/ha. The doses were fue same for both spray and bait treatments and were chosen from experience with previous trials (Caballero et al, 1990(Caballero et al, , 1991Bourner, unpub1ished data). The virus treatments were carried out on 27 May 1991.…”
Section: Insectsmentioning
confidence: 99%
“…Several authors have reported fue successful use of A. segetum granulosis virus (AsGV) for the control of A. segetum and the closely related A. ipsilon in Pakistan (Shah et al, 1979), Denmark (Zethner, 1980) and Spain (Caballero et al, 1990(Caballero et al, , 1991 in tobacco, root crops and maize, respectively. AsGV is also registered as 'Virin-OS', a wettable powder, in fue former Soviet Union for use against A. segetum in cotton (Lipa, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are often detected only when the plants are already severely damaged. Several species of entomopathogenic organisms have been isolated and evaluated as possible biological control agents of cutworm pests (Lipa and Wiland, 1972;Caballero et al, 1991;Steenberg and Ogaard, 2000;Yun et al, 2004;Sevim et al, 2010). However, A. segetum remains a serious threat to agriculture.…”
mentioning
confidence: 99%
“…Two different alphabaculovirus isolates, Agrotis segetum nucleopolyhedrovirus A (AgseNPV-A; also called the Polish isolate) and A. segetum nucleopolyhedrovirus B (AgseNPV-B; also termed the Oxford isolate) (9)(10)(11), as well as the betabaculovirus Agrotis segetum granulovirus (AgseGV) (12), were isolated and characterized from A. segetum larvae. AgseGV was tested extensively as a biocontrol agent for the control of A. segetum in the field (13)(14)(15)(16), and AgseNPV-B has shown its potential as a biocontrol agent under laboratory conditions (13).…”
mentioning
confidence: 99%